KEBIJAKAN DAN STRATEGI PENDIDIKAN NASIONAL UNTUK MEWUJUDKAN GURU PROFESIONAL DALAM MELAKSANAKAN PENDIDIKAN KARAKTER - Kibtiyah, Asriana (Al Tadib : Jurnal Ilmu Pendidikan, 2021)
This artcel is aimed at discussion the national strategy and policy on education. The substance of the convening of education is the formation of characters makes learners ready to live in a society like a human being civilized and dignified. The purpose of education can be achieved if teachers have the professional skills to be part of a profession that is lived. While the existence of the teaching profession should also get the recognition and support of the Government as policy makers and national education strategies. The policy focuses on the existence of an impartial and teachers become key to the success of national education goals in the short and long term.